Cohesion in Finnish EFL essays: Digital analyses and observations on the use of online sources - Niitemaa Marja-Leena (Hungary, 2025)
The study investigated cohesion in Finnish upper-secondary school EFL learners’ essays (N=46). Cohesive devices were digitally identified using TAACO 2.0.4, and robust correlations were run to examine how the devices related to human-rated holistic essay quality. The analyses found that the two most important predictors of writing quality were the use of modifying adverbs and adverbials as referential devices across paragraphs, and a wide array of connectives to organise the text. Further, the writing sessions were video-recorded to examine the role of consulting digital sources in cohesionbuilding. The recorded data suggested that consulting online dictionaries and informational pages assisted cohesion-building if the writer possessed adequate vocabulary knowledge and computer skills and knew how to exploit the sources efficiently. Pedagogically, the findings indicated that learners need more instruction and practice not only on writing cohesive texts but also on how to search for information and lexis effectively.